Desarrollo integrado de yuca: Nuevas perspectivas para agricultores de Ceara - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1991)
The impact of the integrated project for cassava production, utilization, and commercialization in Ceara, Brazil, is assessed. Improved technology was developed in an attempt to reduce the high fluctuations in farinha prices. An alternative market for cassava was sought in the production of dried cassava chips. An agroindustrial model, based on small groups, was adopted, resulting in the establishment of 49 plants, with 11 more in process. Technical assistance will be provided to overcome the limitations posed by the low adoption of improved technology and the poor quality of planting material. Economic benefits have been felt by individual farmers as well as by farmer groups where earnings are distributed among members, used as working capital and as a source of credit for cassava producing members; new sources of employment have also opened up. Chip production, however, reduces employment opportunities for women involved in farinha production. Main beneficiaries of these drying projects are small farmers with 1-2 ha. Key factors in the project`s success have been interinstitutional coordination and training. (CIAT)